CERPEN LAHRU KANGKANG TINIBANIN UDAN SAWENGI DAN SUJEN BETEL KARYA I MADE SUARSA KAJIAN STRUKUR - Gunawan Martha, Putu Eka (Humanis; Volume 6. No. 2. Februari 2014)
This research researching literary Bali modern who shaped short stories. This short story is taken from a collection of short stories "Gede Ombak Gede Angin". This research researching two storiette is Lahru Kangkang Tinibanin Udan Sawengi and sujen Betel. In this study using structural theories used are those of Mr Teeuw, Damono, and Ratna. The Theories uses a combination of several experts opinion literature. Methods and techniques in the study were divided into three stages, namely the stage of providing data by using the method of recording techniques and translation. Stage of data analysis using qualitative and descriptive analytic techniques. Stage presentation of results of data analysis using informal methods are assisted with deductive and inductive techniques. The results obtained in this study is the structure of the short story Lahru Kangkang Tinibanin and Sujen Betel, the formal structures consisting of a variety of language, and style. narrative structure of the short story Lahru Kangkang Tinibanin Udan Sawengi and Sujen Betel composed of the incident, the grooves are used flashbacks and straight, background which includes setting the time, place, and atmosphere, character and characterization, theme, and the the mandate.
Keywords: short stories, structure and.nyentana marriage